P198 Feno and blood eosinophils as biomarkers in predicting asthma exacerbations. (15th November 2017) - Rastogi, S; Bosnic-Antievich, S; Pavord, I; Roche, N; Halpin, D; Bjermer, L; Usmani, O S; Brusselle, G; Ming, S Wan Yau; Halim, S; Gopalan, G; Price, D
Abstract : Introduction and Objectives: Blood eosinophil counts (Bl–Eos) and fractional exhaled nitric oxide concentrations (FeNO) are established biomarkers in asthma. While patients with raised Bl–Eos are at increased risk of asthma exacerbations, it is unclear whether raised FeNO is associated with further increased risk. We sought to determine if raised Bl–Eos combined with raised FeNO was associated with increased frequency of asthma exacerbations. Methods: This was a cross-sectional study of data from the Optimum Patient Care Research Database. Patients included were aged 18–80 years with ≥1 year of continuous electronic health records prior to their most recent FeNO readings, had evidence of asthma, had received ≥1 inhaled corticosteroid prescription, and had Bl–Eos recorded within 5 years of FeNO reading. Cohorts were determined by: Bl–Eos raised (≥0.25×10 9 /L, a cutoff representing the sample mean) and not raised (<0.25×10 9 /L) and, FeNO raised (≥35 ppb) and not raised (<35 ppb). Patients were directly matched on age, sex, and smoking status. Patients with (i) raised Bl–Eos and not raised FeNO, (ii) raised FeNO and not raised Bl–Eos, or (iii) both biomarkers raised were compared with reference patients (neither biomarker raised). Comparison of exacerbations (evidenced by acute oral corticosteroid prescription or unplanned asthma-related hospital attendance) was conducted using conditional Poisson regression. Results: The unmatched study population consisted of 610 patients (mean age 52, 38% male, 46% non-smokers). With 1:1 matching, both the (i) raised Bl–Eos and not raised FeNO cohort (n=186) and the (ii) raised FeNO and not raised Bl–Eos cohort (n=98) demonstrated a trend toward greater exacerbation rates (unadjusted rate ratio: 1.41 [95% CI 0.91, 2.19] and 1.35 [95% CI 0.99 1.84], respectively) vs. reference group. Importantly, however, when both biomarkers were raised (n=53), a significantly greater exacerbation rate was observed (1.72 [95% CI 1.00, 2.93]). Conclusion: The combination of raised FeNO and raised Bl–Eos was associated with a greater exacerbation rate compared with neither biomarker raised. FeNO and Bl–Eos are simple primary care measurements that could reliably predict exacerbation risk for asthma patients. This should be confirmed prospectively in larger populations. Please refer to page A258 for declarations of interest in relation to abstract P198.